Strategi Promosi dalam Pengembangan Pariwisata Lokal di Desa Wisata Jelekong - Setiawan, Nisa Amalina; U., Farid Hamid (TRIKONOMIKA, 2014)
The approach of this research is qualitative, using case study method. The data was obtained through in-depth interview, observation, literature study, and documentation. The data analysis steps used were data reduction, data display, and verification. The purpose of the research is to investigate the promotion strategy of the tourism village of Jelekong, Bandung Regency performed by Kompepar Giriharja. The result of the research shows that Kompepar Giriharja performs promotion mix, i.e., word of mouth, public relations, personal selling, event, exhibition, merchandise, publication, and website. From overall promotion strategy applied by Kompepar Giriharja, the main priority was through event and public relations. The conclusion of this research is Kompepar Giriharja has not formulated comprehensive and integrated promotion strategy.